Krajinski park Tivoli, Rožnik in Šišenski hrib - Erhartič, Bojan (Georitem, 2011)
A quality living environment is an important value of modern life, which is not measured only with GDP, as one of its key factors is also the amount and the quality of green areas, which guarantee a healthier way of living and overall improve the quality of life. We only become aware of these "life-necessities" when their scarcity is almost critical.